2018
DOI: 10.1590/1981-22562018021.170155
|View full text |Cite
|
Sign up to set email alerts
|

Burden, profile and care: caregivers of socially vulnerable elderly persons

Abstract: Objectives: To compare burden and sociodemographic profile and to analyze the care needs of caregivers of elderly persons enrolled in Social Care Referral Centers in a municipal region in the interior of the state of São Paulo, Brazil. Method: A cross-sectional, quantitative-qualitative study was carried out. A sociodemographic questionnaire, the Zarit Burden Scale and three open questions regarding care needs were applied. The quantitative data were analyzed by descriptive statistics and the correlation test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
30

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 20 publications
1
28
0
30
Order By: Relevance
“…17 In addition, it is needed the support of this population by means of the public equipments. 22 Among the formal caregivers, 66.7% reported that they did not reside with the elderly.…”
Section: Profile Of Caregivers Of Elderly Peoplementioning
confidence: 99%
“…17 In addition, it is needed the support of this population by means of the public equipments. 22 Among the formal caregivers, 66.7% reported that they did not reside with the elderly.…”
Section: Profile Of Caregivers Of Elderly Peoplementioning
confidence: 99%
“…Nessa categoria, os estudos apontam a necessidade de readaptação e reorientação das políticas públicas que fornecem suporte formal aos cuidadores familiares 23,[42][43][44] . Propõe-se estabelecer programas sociais preventivos destinados a desenvolver áreas de lazer para os idosos destinado a apoiar os cuidadores familiares e simultaneamente beneficiar a qualidade de vida de todos 43 .…”
Section: Estratégias De Enfrentamento No âMbito Social: Políticas Púbunclassified
“…investigação, constatou-se o predomínio de cuidadores do sexo feminino na faixa etária de 36 a 50 anos, casados(as) ou convivia com companheiro(a), achados que corroboram com outros estudos (6,7) .Por se tratar de mulheres casadas e com companheiro inferese que tal condição associada à atividade de cuidado com demandas crescentes, pode levar a sobrecarga biopsicoemocional e comprometimento da relação conjugal.…”
Section: Nessaunclassified
“…O grau de parentesco do cuidador informal com o adoecido era na maioria filho(a) e esposo(a), assim como encontrado em outras pesquisas (7,8) . Sendo assim, o tempo dispensado ao cuidado e o vínculo que se estabelece entre o cuidador e o ente cuidado pode aumentar e gerar no cuidador informal, uma sobrecarga física e emocional pela complexidade dos cuidados (19) .…”
Section: Nessaunclassified
See 1 more Smart Citation